Associations of Ultra-Processed Food Intake with Body Fat and Skeletal Muscle Mass by Sociodemographic Factors - Sukyoung Jung; Jaehee Seo; Jee Young Kim; Sohyun Park (Diabetes & Metabolism Journal, 2024)
Background The effects of excessive ultra-processed food (UPF) consumption on body composition measures or sociodemographic disparities are understudied in Korea. We aimed to investigate the association of UPF intake with percent body fat (PBF) and percent appendicular skeletal muscle mass (PASM) by sociodemographic status in adults. Methods This study used data from the Korea National Health and Nutrition Examination Survey 2008–2011 (n=11,123 aged ≥40 years). We used a NOVA system to classify all foods reported in a 24-hour dietary recall, and the percentage of energy intake (%kcal) from UPFs was estimated. PBF and PASM were measured by dual-energy X-ray absorptiometry. Tertile (T) 3 of PBF indicated adiposity and T1 of PASM indicated low skeletal muscle mass, respectively. Multinomial logistic regression models were used to estimate odds ratios (OR) with 95% confidence interval (CI) after adjusting covariates. Results UPF intake was positively associated with PBF-defined adiposity (ORper 10% increase, 1.04; 95% CI, 1.002 to 1.08) and low PASM (ORper 10% increase, 1.05; 95% CI, 1.01 to 1.09). These associations were stronger in rural residents (PBF: ORper 10% increase, 1.14; 95% CI, 1.06 to 1.23; PASM: ORper 10% increase, 1.15; 95% CI, 1.07 to 1.23) and not college graduates (PBF: ORper 10% increase, 1.06; 95% CI, 1.02 to 1.11; PASM: ORper 10% increase, 1.07; 95% CI, 1.03 to 1.12) than their counterparts. Conclusion A higher UPF intake was associated with higher adiposity and lower skeletal muscle mass among Korean adults aged 40 years and older, particularly in those from rural areas and with lower education levels.